2016
DOI: 10.35790/ecl.4.2.2016.14216
|View full text |Cite
|
Sign up to set email alerts
|

Kesehatan telinga mahasiswa Sekolah Polisi Negara Karombasan Manado

Abstract: Ear is one of the five senses that functions as hearing and body balance device. The health status of human ear is influenced by lifestyle, activities, and environmental factors. Noise is one of the hazardous physical factors that could cause hearing problems ranging from temporary to permanent deafness depending on the intensity of noise, duration of exposure, and individual sensitivity towards noise. Ear health status can be determined through investigation problems or abnormalities of the ear and the hearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Based on gender, samples of this study were all male (100%). A prior study by Mahardana et al 5 all samples were male, by Sasongko 18 all samples were male, and by Cetin et al 1 also all samples were male. The samples in this study and in prior studies were all male due to the fact that the population of East Java SPN students were all male.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Based on gender, samples of this study were all male (100%). A prior study by Mahardana et al 5 all samples were male, by Sasongko 18 all samples were male, and by Cetin et al 1 also all samples were male. The samples in this study and in prior studies were all male due to the fact that the population of East Java SPN students were all male.…”
Section: Discussionmentioning
confidence: 88%
“…A study by Mahardana et al 5 on 100 Singaraja SPN students showed acoustic trauma of 11%. A research in Makassar, in 2001 directed towards Mobile Brigades, SPN students, and the Municipal Police members, obtained an incidence of 16.67% trauma acoustic.…”
Section: Statistical Results Of Pearson Correlationmentioning
confidence: 96%
See 2 more Smart Citations